Introduction of Configurational Indicators for Distribution Network Optimality Based on a Zoning Methodology - Mojtaba Gilvanejad; Mostafa Goodarzi; Hamideh Ghadiri (AUT Journal of Electrical Engineering, 2021)
The configuration of electrical distribution network may alter upon the changes in the load density and the load distribution in the region. Regional climatic conditions affect the rating of the components in the distribution network. Therefore, they have some influences on the network configuration as well. These two affecting factors (electrical load and climate) are not directed by the system operator or designer. Hence, it is pleasurable to find an appropriate network plan to satisfy the load requirements as well as the climate undesirable influences in real operating conditions. This paper is aimed to find some quantitative relevancies between the network configuration and the affecting parameters (i.e. climatic conditions, load density, load profile and loss factor) to achieve this goal. It has tried to define some factors to quantify the network configuration in order to simplify judgement about the design quality of the network. This means that these factors can be used as quantitative benchmarks that help network planner to understand which parts of the existing network are not in accordance with the optimal configuration. This study is conducted through statistical analysis on real data attained from several networks in different climatic conditions and different load situations. The idea is examined via performing the network design optimizations on 35 scenarios for the networks located in 5 different areas. Results are presented in tables and figures that are informative and practical for the network engineers to design and operate the distribution system in different loading conditions and climatic situations.